The Impact of Self-Management Program on Quality of Life and Neurological Function in Stroke Patients: A Systematic Review - Muhith, Abdul; Magfirah Supu, Nurul (Journal of Applied Nursing and Health, 2024)
Background: Stroke is the leading cause of death and disability with a high global prevalence, including in Indonesia, which has the second highest stroke mortality rate in Asia. Self-management is a promising rehabilitation strategy to improve post-stroke patients' quality of life (QoL) and neurological function. However, the results of previous studies are still varied and inconsistent. Purpose: To evaluate evidence from randomized controlled trials (RCTs) regarding the effectiveness of self-management programs in enhancing quality of life (QoL) and neurological function among stroke patients, to provide evidence-based recommendations for clinical practice Methods: The systematic review screened RCT studies from PubMed, Scopus, ScienceDirect, and ClinicalKey databases published in the last 5 years. The inclusion criteria are based on the principle of PICOS, with interventions in self-management programs, QoL outcomes, and neurological functions—quality assessment using the CASP Checklist for RCTs. Results: Of the 2020 articles identified, 11 studies with 3,892 participants met the criteria. The self-management programs used varied, including telerehabilitation, physical exercise, personalized music, and multifaceted interventions. The duration of the program ranges from 3 to 52 weeks. Most studies showed significant improvements in QoL and neurological function of stroke patients. Conclusion: Self-management programs are effective in improving the QoL and neurological function of stroke patients, with effectiveness affected by the type of intervention and the program duration. These findings support the implementation of self-management programs in evidence-based stroke rehabilitation.